How much does elective cardioversion increase the risk of ischaemic stroke compared to the baseline risk in atrial fibrillation? A nationwide study - Itäinen-Strömberg, Saga; Lehto, Mika; Halminen, Olli; Haukka, Jari; Putaala, Jukka; Lehtonen, Ossi; Mustonen, Pirjo; Linna, Miika; Hartikainen, Juha; Airaksinen; Kari Eino Juhani; Teppo, Konsta; et al. (Oxford University Press, 2026)
Aims
Patients with atrial fibrillation (AF) undergoing cardioversion (CV) are exposed to increased risk of ischaemic stroke (IS), but the exact magnitude is unknown. We compared IS rates during the post-CV period with the long-term risk in AF patients using guideline-recommended anticoagulation therapy.
Methods and results
This nationwide register-based study included all AF patients undergoing first-ever elective CV between 2012 and 2018 in Finland. Breakpoint analysis identified a cut-off point in the IS rate at 2 weeks after CV. Follow-up was split into two intervals: the immediate 2-week post-CV period and the subsequent period up to 360 days. Stroke rates were calculated, and incidence rate ratios were estimated with Poisson regression. Interactions between the two follow-up periods and conventional IS risk factors as well as anticoagulation treatment were assessed. A total of 9625 patients were identified (mean age 67.7 ± 9.9 years, 61.2% men, mean CHA2DS2-VA score 2.2 ± 1.4). Warfarin was used in 6245 (64.9%) and non-vitamin K oral anticoagulants in 3380 (35.1%) patients. Overall, 92 (1.0%) patients experienced IS during the year after CV. Breakpoint analysis and survival plot displayed a higher incidence of IS within the first 2 weeks after CV, stabilizing thereafter to a consistent level. The adjusted IS rate during the first 2 weeks was 7.5-fold (95% confidence interval: 4.8–11.8) compared to the subsequent IS rate. This excess risk was independent of the anticoagulation type or conventional stroke risk factors.
Conclusion
The rate of IS was roughly seven times higher during the first 2 weeks after elective CV compared to the subsequent 360 days.